1998
DOI: 10.1016/s0006-3495(98)77590-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Creatine Kinase upon Substrate Binding

Abstract: Small-angle x-ray scattering was used to investigate structural changes upon binding of individual substrates or a transition state analog complex (TSAC; Mg-ADP, creatine, and KNO3) to creatine kinase (CK) isoenzymes (dimeric muscle-type (M)-CK and octameric mitochondrial (Mi)-CK) and monomeric arginine kinase (AK). Considerable changes in the shape and the size of the molecules occurred upon binding of Mg-nucleotide or TSAC. The radius of gyration of Mi-CK was reduced from 55.6 A (free enzyme) to 48.9 A (enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 34 publications
9
48
0
Order By: Relevance
“…2). Hence, in line with what has been described for CK and AK (25,33,34), binding of the guanidino substrate is not the main determinant of the conformational change cascade observed for the TSA complex.…”
Section: More Insights Into Phosphagen Specificity-althoughsupporting
confidence: 83%
See 1 more Smart Citation
“…2). Hence, in line with what has been described for CK and AK (25,33,34), binding of the guanidino substrate is not the main determinant of the conformational change cascade observed for the TSA complex.…”
Section: More Insights Into Phosphagen Specificity-althoughsupporting
confidence: 83%
“…The crystal structures of CK-, AK-, and GK-TSA as well as NMR and mass spectrometry studies show that this structural rearrangement is accompanied by the stabilization of a C-terminal flexible loop that shields the active site from the solvent (14,19,20,23,24,27,30,31). The PK-TSA structure is closed, and the bound compounds are locked in proper alignment for the in-line phosphoryl transfer (23,26,(32)(33)(34)). An invariant cysteine (Cys 268/631 in SmTK) and an invariant glutamate (Glu 222/585 in SmTK) contribute to the stabilization of the guanidylic acceptor and maximize the catalytic reaction (20,35).…”
mentioning
confidence: 99%
“…Comparing the UcLK-ADP structure with the LpAK-TSAC, 12 of 13 hydrogen bonds and salt bridges (68) between ADP and enzyme are conserved. Such consistency was unexpected, because UcLK-ADP and LpAK-TSAC are in the open and closed state conformations, respectively, which AK and CK solution scattering indicates is determined primarily by nucleotide binding (65,66). Mg 2ϩ , required for ADP-or ATPinduced changes to solution scattering, was present in the crystallization solution but was not coordinated to the nucleotide in the UcLK-ADP structure.…”
Section: Comparison Of Open and Closed States In The Nucleotide Bindimentioning
confidence: 99%
“…Furthermore, the extent of subdomain 3 reorientation upon nucleotide binding appears finely balanced. Although the prevalence of closed form, ADP-bound crystal structures and solution scattering (65,66) suggests that closed forms might generally be favored slightly in the presence of ADP, the three intermediate/ open form exceptions suggest that the energetics are finely balanced. NMR relaxation dispersion has shown that subdomain 3 exhibits millisecond exchange dynamics in the substrate-free state of LpAK (22).…”
Section: Nucleotide Binding and Dynamic Loopsmentioning
confidence: 99%
“…Although, the unfolding of CK during thermal denaturation is signi®cantly a ected by the presence of Mg 2+ (Fig. 6), free Mg 2+ did not a ect the structure of native CK [24] as seen in the data that showed that free Mg 2+ did not a ect the l max of CK (Fig.7). Thus, further decreases in the catalytic activity of CK in the presence of Mg 2+ during thermal denaturation occurred because Mg 2+ enhanced the conformational changes of CK and enhanced the denaturation of CK for those conditions.…”
Section: Discussionmentioning
confidence: 83%